Proposals submitted by the UK Government to the International Committee for the Application of the Agreement Regarding Non-Intervention in Spain - International Committee for the Application of the Agreement Regarding Non-intervention in Spain
1937-07-14 018b-0056-001 292/946/18b/56(i)